Strategies for Community-Based Total Sanitation in Improving Hygiene Behavior: A Case Study of Purwosari II Village, Tamban District - Azwari, Trisylvana; Dewi, Avela; Ariyani, Erma; Aulia, Aulia; Rahman, Fathur; Prismadanu, Aliffathur (Universitas Teuku Umar, 2025)
This study looks at how the Community-Based Total Sanitation (CBTS) Program is being used in Purwosari II Village, Tamban Sub-district, Barito Kuala Regency, to find effective ways to change the community’s hygiene habits and enhance public health. The program aims to improve sanitation and health through five key pillars. However, challenges in changing hygienic behavior remain significant in practice. The methodology used is a qualitative approach, with data collection techniques including observation, interviews, documentation, and focus group discussions (FGD). A SWOT analysis was conducted to identify internal and external factors affecting the program’s implementation. The results show that although sanitation facilities such as communal toilets have been built, their distribution is uneven, and some people still maintain unhygienic behavior. Factors influencing such behavior include poorly developed policies, a lack of specialized CBTS cadres, and the community's reliance on government physical assistance. Based on these findings, suggested strategies include strengthening written policies, improving inter-sectoral coordination, and empowering the community through training and triggering healthy behaviors at the community level. It is hoped that these measures will make the CBTS program in Purwosari II Village more effective in creating behavior change and sustainably improving public health.